تعليم فن الخط في منظمة جمعية الخطاط بمعهد منبع العلوم بتا-بتا الإسلامي باميكاسان مادورا - Ali Makki; Ahmad Fauzun Karim; Utari Dwi Mayasari (Universitas Negeri Malang, 2022)
Sheikh Shams Al-Din Al-Afkani held that the calligraphy was a single letter in its place and how it was formulated in a written composition or written in a written form. Of the importance of calligraphy: Calligraphy is not limited to the skill of drawing and writing alone, but it is related to spiritual insight. Calligraphy pleads to protect the heart, speech, ideas, and behavior of society. In learning precious social values ​​of following, imitation, competence, obedience, orderliness, benefit, and appreciating the production of others. Despite the great importance of calligraphy, unfortunately, its study and education is neglected and most people do not care about it. As well as the widespread research does not deal with much research and depth. This research presents to the readers to reveal the process of teaching calligraphy in the Calligrapher Association at the Institute of the Source of Sciences Pta-Pta Bamikasan Madura as a contribution to increasing the wealth of scientific research on the art of teaching calligraphy and its advantages and shortcomings. The researcher used for this research the approach of scientific research is qualitative research with the type of case study. The three methods of data collection are interview, observation and documentation. This scientific research has reached the conclusions that teaching the art of calligraphy in it takes place in three stages: pre-education, implementation of education, and evaluation of education. As for the advantages, most of them are dispensed for a long time and it is cheaper for the others. The shortcomings, including the lack of puberty to the maximum and perfection.